Effects of systemic administration of the retinoid Isotretinoin on bone tissue: A narrative literature review - Maria Júlia Bento Martins Parreira; Bruna Trazzi Pagani; Matheus Bento Medeiros Moscatel; Daniela Vieira Buchaim; Carlos Henrique Bertoni Reis; Beatriz Flávia de Moraes Trazzi; Acácio Fuziy; Rogerio Leone Buchaim (AIMS Bioengineering)
Isotretinoin is an oral medication commonly utilized to treat severe acne. It belongs to the class of retinoids and is a synthetic form of vitamin A. Possible changes in bone tissue associated with the systemic administration of Isotretinoin for long periods and in high doses, such as hypercalcemia, osteopenia, diffuse hyperostosis, or even skeletal deformities, are reported in scientific studies. The objective of this literature review was to analyze the available scientific literature on the systemic administration of Isotretinoin and its effects on bone tissue. To this end, articles that demonstrate effects of Isotretinoin on bone metabolism, bone mineral density, bone formation, and resorption, in addition to possible changes generated in this tissue were considered valid for inclusion in this literature review. The search for articles that fit the premise of this work was carried out in the PubMed/MEDLINE database. In a preliminary search, 85 articles were obtained; after in-depth investigation and checking of the inclusion and exclusion criteria, 21 articles were selected, with 17 articles reporting the effect of systemic administration of Isotretinoin in humans and four articles analyzing the effect generated by this substance systemically administrated in animals, more specifically in rats. After analyzing the selected articles, it was possible to observe several reports on hyperostosis or even changes in the formation of bone structures in human patients. Concerning animals, the largest number of studies addressed the changes caused in the formation or development of bone structures by the systemic administration of Isotretinoin. From the current analyses, and given the wide use of Isotretinoin, it is necessary to know its viability and influence on tissues. Its clinical efficacy seems to overcome any of the skeletal side effects observed; however, more studies are necessary to properly evaluate and prove the effects generated on bone tissues as well as other structures.